Pengaruh Motivasi dan Gaya Kepemimpinan terhadap Prestasi Karyawan dengan Metode Structural Equation Modelling - Aris Susanto; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2017)
PT. Santos Premium Creamer is a great company in the area of Sidoarjo, food companies and one of the largest producers of creamer in Sidoarjo, the process of using tech machines. Soit needs human resourcehas the ability as well asinsight into the science of running machines. Supporting career PT.Santos Premium Creamer is one of the main requirements of education, the Company provides the opportunity for employees at the level of assistant to resume his education from vocational to higher education as one of the main requirements if later there is promotion of employees. So with the career path in PT. Santos Premium Creamer, motivate employees to college. PT. Santos Premium Creamer consists of several departments of which the production department, where in every part of the patriarch with different people and have different leadership styles as well. Included response to the employees in the department who enrolled. This study was to determine whether the motivation and leadership style affect the achievement of employees of PT. Santos Premium Creamer is currently studying by using SEM (Structural Equation Modelling). Obtaining results that affect the achievement of employee motivation PT.Santos Premium Creamer is currently studying. Leadership style has no effect on employee performance PT.Santos Premium Creamer is currently studying. Good leadership style for leadership in PT.Santos Premium Creamer is a style of leadership that has the ability to work closely matching